SINERGISITAS PEMANGKU KEPENTINGAN DALAM MENGIMPLEMENTASIKAN INKLUSI KEUANGAN PADA PERBANKAN SYARIAH DI INDONESIA - Nengsih, Novia (CV. Doki Course and Training, 2023)
This study aims to analyze the synergy of stakeholders in supporting the implementation of financial inclusion in Islamic banking in Indonesia. This research is a field research using a qualitative approach. The research results show that Bank Indonesia and the Financial Services Authority (OJK) make policies that are responsive and synergistic in supporting financial inclusion. Bank Indonesia formulated the National Financial Inclusion Strategy (SNKI) as a reference for implementing financial inclusion in Indonesia. The six pillars of the National Strategy for Financial Inclusion (SNKI), namely financial education, public financial facilities, mapping of financial information, supporting policies/regulations, intermediation and distribution channels as well as consumer protection, were created in order to support financial inclusion. Bank Indonesia, which has now been handed over to the OJK, has also made a policy on the obligation to provide banking financing of at least 20 percent to be channeled to Micro, Small and Medium Enterprises (MSMEs). The Financial Services Authority (OJK) supports the implementation of financial inclusion through 3 pillars which are translated into several activities. The three pillars are education programs and national financial literacy campaigns, strengthening financial literacy infrastructure, and developing affordable financial products and services. Abstrak Penelitian ini bertujuan untuk menganalisis sinergisitas pemangku kepentingan dalam mendukung implementasi inklusi keuangan pada perbankan syariah di Indonesia. Penelitian ini merupakan penelitian lapangan menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa Bank Indonesia dan Otoritas Jasa keuangan (OJK) membuat kebijakan yang responsif dan sinergis dalam mendukung inklusi keuangan. Bank Indonesia merumuskan Strategi Nasional Keuangan Inklusif (SNKI) sebagai acuan pengimplementasian financial inclusion di Indonesia. Enam pilar Strategi Nasional Keuangan Inklusif (SNKI), yaitu edukasi keuangan, fasilitas keuangan public, pemetaan informasi keuangan, kebijakan/peraturan pendukung, intermediasi dan saluran distribusi serta perlindungan konsumen, dibuat dalam rangka mendukung financial inclusion. Bank Indonesia yang sekarang diserahkan kepada OJK juga membuat kebijakan kewajiban pemberian pembiayaan perbankan minimal 20 persen disalurkan kepada Usaha Mikro Kecil dan Menengah (UMKM). Otoritas Jasa Keuangan (OJK) mendukung pengimplementasian financial inclusion melalui 3 pilar yang dijabarkan ke dalam beberapa kegiatan. Tiga pilar tersebut adalah program edukasi dan kampanye nasional literasi keuangan, penguatan infrastruktur literasi keuangan, dan pengembangan produk dan layanan jasa keuangan yang terjangkau.